A Double Allylation Strategy for Gram‐Scale Guaianolide Production: Total Synthesis of (+)‐Mikanokryptin. (3rd January 2017) - Hu, Xirui; Xu, Silong; Maimone, Thomas J.
Abstract: With over 5000 members isolated to date, sesquiterpene lactones represent a prolific source of medicinal agents with several derivatives in human clinical trials. The guaianolides, a major subset of this group, have been intensely investigated from both medicinal and chemical‐synthesis perspectives for decades. To date, the myriad stereochemical permutations presented by this enormous family have precluded the synthesis of many unique members. Herein we report the total synthesis of the trans ‐fused 8, 12‐guaianolide (+)‐mikanokryptin in 10 steps from (+)‐carvone. Notably, this synthesis is the first gram‐scale total synthesis of a guaianolide natural product.